An analysis of the legislation, published accounts and operating statistics of the Great Southern Railways Co., 1924-1937 - Shields, B. F. (Statistical and Social Inquiry Society of Ireland, 1938)
The unsatisfactory financial position of the railways lying wholly within the Saorstat forced the Government to take measures for their radical reorganisation and more effective business control. This paper will review the results of this reorganisation.
Read on Wednesday, 25th May, 1938
Keywords: Great Southern Railway; Railway accounts; 314.15